Language and identity in the Arab world - Mehta, Sandhya Rao; Al Rashdi, Fathiya (Routledge studies in language and identity, 2023)
"Language and Identity in the Arab World explores the inextricable link between language and identity, referring particularly to the Arab world. Spanning from Indonesia to the United States, the Arab world is here imagined as a continually changing one, with the Arab diaspora asserting its linguistic identity across the world. Crucial questions on transforming linguistic landscapes, the role and implications of migration, the impact of technology on language use are explored by established and emerging scholars in the field of applied and socio-linguistics. The book asks such crucial questions as how language contact affects or transforms identity, how language reflects changing identities among migrant communities, and how language choices contribute to identity construction in social media. As well as appreciating the breadth and scope of the Arab world, this anthology focuses on the transformative role of language within indigenous and migrant communities as they negotiate between their heritage languages and those spoken by the wider society. Investigating the ways in which identify continues to be imagined and re-constructed in, and among Arab communities, this book is indispensable to students, teachers and anyone who is interested in language contact, linguistic landscapes, minority language retention as well as the intersections of language and technology"--